“Whose Inquiry is this Anyway?” Money, Power, Reports and Collaborative Inquiry - Elizabeth Kasl; Lyle Yorks (Adult Education Research Conference, 2008)
Adult educators who use collaborative/cooperative inquiry (CI) in institutional settings must be aware of potential corrupting influences from money, power and reporting requirements.
Keywords: collaborative/cooperative inquiry; institutional accountability; power inequity